Acupuncture reduced apoptosis and up-regulated BDNF and GDNF expression in hippocampus following hypoxia–ischemia in neonatal rats. (22nd August 2015) - Zhang, Yong; Lan, Rui; Wang, Jun; Li, Xiang-Yun; Zhu, Deng-Na; Ma, Yun-Zhi; Wu, Ji-Tao; Liu, Zhen-Huan
Abstract: Ethnopharmacological relevance: Acupuncture attenuates neuronal damages following ischemia. Aim of the study: The purpose of the present study was to investigate the beneficial effects of acupuncture on hypoxia–ischemia induced brain damages in neonatal rats. Materials and methods: Male postnatal 7 days rats were randomly divided into 3 groups: sham control (sham), hypoxia–ischemia (HI), and HI plus acupuncture treatment (HI+Acu). The rats in HI and HI+Acu groups were submitted to model of neonatal HI, established by occluding the left common carotid artery followed by a 3.5 h period of hypoxia (8% O2 –92% N2 ). At 24 h after HI, animals were stimulated by acupuncture treatment once a day and the treatment continued during 4 weeks, 5 days/week. Behavioral functions, learning and memory ability, and body weight were observed at different time-points after HI. DNA fragmentation assay were performed with TUNEL staining to evaluate apoptosis and expression levels of mitochondrial Bcl-2, mitochondrial Bax, Cleaved caspase 3, Cleaved caspase 9 in the damaged hippocampus were detected by western blotting 28 days following HI. GDNF, BDNF levels in hippocampus were also determined. Results: The results showed that acupuncture significantly promoted growth and development, improved neurobehavioral function, learning and memory ability after 20 days' treatment. Furthermore, we obtained one interesting finding that acupuncture attenuated cellular apoptosis and up-regulated GDNF and BDNF levels in hippocampus. Conclusions: All of these results suggest that acupuncture as a potential treatment may exert neuroprotective effects via inhibiting cellular apoptosis, increased GDNF and BDNF expression levels in rat hippocampus experiencing HI. Graphical abstract: